(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article addresses the role of children in Early Childhood Education, with an emphasis on the stages from nursery to kindergarten, seeking to understand the pathways that enable the active and participatory role of children during this fundamental period of human development. The research was conducted through a bibliographical study that analyzed works, scientific articles, and official documents related to child development, the pedagogy of protagonism, and inclusive educational practices. The methodology identified the main aspects that contribute to the recognition of children as subjects of rights and agents of their own learning, highlighting the role of the educator as a mediator sensitive to children’s multiple languages. The results demonstrate that active listening, intentional organization of spaces, flexibility in routines, and the appreciation of play are essential elements for fostering children’s autonomy, creativity, and participation. Furthermore, the importance of building emotional bonds and partnering with families to consolidate a democratic and respectful educational practice is emphasized. The article concludes that child empowerment represents an ethical and pedagogical commitment that transforms early childhood education into a meaningful learning space, expanding the possibilities for comprehensive development and strengthening identity and citizenship from the earliest years of life. This promotes a child-centered education that recognizes and enhances children’s skills, interests, and needs, contributing to the development of autonomous, critical, and participatory individuals.